The Future of Sustainable Culinary: From Local Ingredients to the Traveler's Table - Ainiya, Sri Khusnul; Zahri, Shafira Syahlaa Delia Dani (Gastronary, 2025)
This study investigates how local ingredients can underpin the development of sustainable culinary practices in Yogyakarta and their influence on tourism and the local economy. Utilizing a qualitative approach based on the Miles and Huberman framework, the research focuses on local culinary entrepreneurs, farmers, tourists, and other stakeholders in Yogyakarta. Participants were chosen through purposive sampling and included 15 restaurant owners specializing in local ingredients, 10 farmers from the regions of Bantul, Sleman, and Gunungkidul, as well as 20 domestic and international tourists. Data were gathered through in-depth interviews, participatory observations, and document analysis. The results indicate that using local ingredients in traditional dishes like gudeg and thiwul not only helps preserve cultural heritage but also boosts restaurant revenue by as much as 25% and creates new employment opportunities for farmers. Both domestic and international tourists expressed a strong preference for authentic, locally-sourced dishes due to the cultural experience they provide. Nevertheless, challenges such as inconsistent availability of local ingredients, inadequate logistics, and low consumer awareness of sustainability impede progress. The study concludes that effective collaboration among government entities, businesses, and communities is vital to addressing these challenges and enhancing Yogyakarta's status as a sustainable culinary tourism destination. Consequently, the findings offer valuable insights for developing sustainable culinary systems in other regions.